Thematic learning for character excellence: Developing an education module for primary students - Soepudin, Usep; Budimansyah, Dasim; Hidayat, Mupid; Somad , Momod Abdul (Universitas Negeri Yogyakarta, 2025)
This study designs and develops the Citizenship Education model to strengthen students' character. We need to continuously create several learning models that reinforce students' positive character. They stay enthusiastic about finishing the lecture on time and do not let life's challenges erode their spirit. They used development research. We obtain the analysis results from several stages: first, we identify problems and carry out task analysis; second, we conclude learning objectives during the design phase; third, we create patterns and utilise digital media in development; fourth, we apply the designed learning pattern in implementation; and fifth, we observe whether the created learning pattern aligns with our initial beliefs during evaluation. The development of the ADDIE instructional model leads to the next stage, which adapts to create the Citizenship Education learning model known as MPC (Modification of Project Citizen). This model focuses on digital media and develops Citizenship Education to strengthen students' character. This study introduces a novel Citizenship Education learning model that utilises interactive digital media to effectively deliver material and systematically shape students' citizenship character in the context of the digital era.